Green triangular co-operation - Casado-Asensio, Juan,Pelechà Aigües, Néstor,Piefer-Söyler, Nadine (OECD Publishing, 2019)
This report showcases how triangular co-operation can contribute to achieving ‘green’ objectives (e.g. on climate change mitigation, climate change adaptation, biodiversity, desertification, and local environmental issues). Data collected through an OECD survey on triangular co-operation (2015) and desk research uncovered 224 triangular projects targeting green objectives, involving 91 countries and international organisations, out of a total of 658 triangular co-operation projects for the period 2014-18. Given the available evidence (data, evaluations and interviews with project managers), the report shows that triangular activities can deliver green goals in innovative, flexible and cost-effective ways within and across regions – and thus could help accelerate implementation of the Sustainable Development Goals and other international green agreements (e.g. the Paris Agreement). Nevertheless, there are several barriers that prevent further deployment of this modality, including lack of awareness on triangular co-operation among the different green communities, insufficient evidence on the potential of green triangular co-operation, and few dedicated vehicles that can pilot and scale-up successful initiatives. The report proposes a number of recommendations for policy makers to overcome these barriers.
10.1787/d81d884a-en
Keywords: Amtsdruckschrift; Graue Literatur; Development; green; triangular development co-operation; environment; climate change mitigation and adaptation; biodiversity; green policy; Green growth